2018
DOI: 10.1089/vbz.2017.2202
|View full text |Cite
|
Sign up to set email alerts
|

First Evidence of Vertical Infection of Dengue Virus 2 inAedes aegyptiMosquitoes from Sinaloa, Mexico

Abstract: Fourteen pools of Aedes aegypti larvae collected within the urban area of Culiacán, Sinaloa, were analyzed by RT-PCR. The results demonstrate, for the first time, the vertical infection of serotype-2 dengue virus (DENV-2) in Sinaloa, Mexico, suggesting that Ae. aegypti acts as a natural reservoir of DENV-2 in this region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…Under laboratory conditions, the filial infectious rate of Zika virus in Ae. aegypti mosquitoes ranged from 4.9 to 24.6, depending on the strain of the virus tested ( 31 ), which corroborates that our results are comparable to the MIRs reported for other Zika viruses and other flaviviruses, including DENV ( 32 , 33 ).…”
Section: Discussionsupporting
confidence: 91%
“…Under laboratory conditions, the filial infectious rate of Zika virus in Ae. aegypti mosquitoes ranged from 4.9 to 24.6, depending on the strain of the virus tested ( 31 ), which corroborates that our results are comparable to the MIRs reported for other Zika viruses and other flaviviruses, including DENV ( 32 , 33 ).…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, DENV-2 was identified in three Ae. aegypti larvae pools in Quintana Roo State and two pools in Sinaloa State [16,18]. However, in none of these studies, virus infection was confirmed by virus isolation.…”
Section: Discussionmentioning
confidence: 90%
“…Similarly, in Sinaloa, Mexico, RT-PCR and semi-nested PCR were used to identify DENV-2 in 2 of 14 pools of Ae. aegypti larvae (308 larvae) [ 41 ] and DENV-4 in 15 of 36 pools of Ae. aegypti larvae (672) [ 42 ] collected from the field with MIRs of 6.49 and 22.32, respectively.…”
Section: Introductionmentioning
confidence: 99%